Tautomeric, spectroscopic, electronic and NLO analyses of purpald (4-amino-3-hydrazino-5-mercapto-1, 2, 4-triazole). (August 2022) - Gökce, Halil; Ceylan, Serkan; Öztürk, Nuri; Sert, Yusuf
Abstract: Thione and thiol tautomeric structural forms of 4-Amino-3-hydrazino-5-mercapto-1, 2, 4-triazole (purpald) were theoretically analyzed based on energetic and molecular structural geometry by using the DFT/B3LYP method with the 6–311++G(3df, 3pd) basis set. The existence of the inter-molecular H-bond or close contact interactions within solid state crystal packing diagram was determined by Hirshfeld surface analysis. The experimental and theoretical investigations on the NMR chemical shifts were used for determination of more dominant tautomeric form between thione and thiol structures. The characteristic vibrations of functional groups within the compound were analyzed with IR and Raman wavenumbers. The experimental and computational UV spectral study was made to examine nature of the intra-molecular electronic transitions within DMSO solution phase. Some global quantum mechanical descriptors were determined with FMOs (HOMO and LUMO) investigation. The presence of hyperconjugation interactions within NBO analysis helped to explain thione-thiol tautomeric equilibrium and inter-molecular N4-H15···N8′ and N7′-H12′···S9 interactions within thione dimeric form. The reactive sites of all tautomeric forms were examined with MEP surface analysis. The static NLO properties were theoretically investigated to test whether all tautomeric forms have a non-linear optical material profile. A theoretical investigation on the molar volume, dielectric constant and refractive index of the compound was carried out at mentioned computational level of theory. Comparison and detailed presentation of the structural and spectral experimental and calculated related properties of the compound were done in this study. Graphical Abstract: ga1 Highlights: Tautomeric structure of purpald was investigated with the B3LYP/6–311++G(3df, 3pd) level. Interactions within crystal packing were supported by Hirshfeld surface analysis. The spectral characterization was performed by both experimental and computational methods. Electronic properties (HOMO, LUMO, NBO and MEP) were studied. NLO profile was determined for all tautomeric forms.